Two new genera with descriptions of three new species of Phaneropterinae (Orthoptera: Tettigoniidae) from China - Liu, Chun-Xiang; Kang, Le (Zootaxa, 2008)
Two new genera, Parapelerinus gen. nov., and Conversifastigia gen. nov. with three new species, P. ensatus sp. nov., P. emarginatus sp. nov., and C. gressitti sp. nov. are described from Southern China. Principal taxonomic and diagnostic characters including structure of head, tegmen, stridulatory file of male, male and female apex are illustrated. Parapelerinus is distinguished from other related genera by the sword-like ovipositor, which is very uncommon in the subfamily Phaneropterinae. The species of Conversifastigia gen. nov. possess a pyramidal fastigium frontis, which is not present in related genera.